Pengaruh Prinsip-Prinsip Good Corporate Governance Pada Kinerja Keuangan Koperasi di Kabupaten Badung - Saputra, Putu Wawan; Noviari, Naniek (E-Jurnal Akuntansi, 2018)
Increasing competition is forcing cooperatives to apply appropriate governance to provide good services in order to increase consumer confidence. The governance in question is the implementation of good corporate governance (GCG). This study aims to see whether the financial performance of cooperatives has reflected the application of good GCG. This research was conducted on cooperatives located in Badung regency. The number of samples taken as many as 31 cooperatives, with the method of non probability sampling, namely purposive sampling. Application of GCG principles was measured using questionnaires. The financial performance of the cooperative is determined by the results of the assessment conducted by the Office of Cooperatives, SMEs and Trade of Badung Regency. Analyzer used in this research that is descriptive statistic test, test instumen research, test of classical assumption and multiple linear regression test. The results showed that the GCG Principles have a positive effect on the financial performance of cooperatives in Badung regency. Keywords: koperasi,, financial performance, good corporate governance